TYPES OF CODE SWITCHING FOUND IN DEDDY CORBUZIER'S PODCAST WITH CHEF JUNA - Sari, Kadek Sintya Ardayanti (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2023)
These days, code-switching is a common occurrence on media social such as Facebook, twitter, instagram, and YouTube. The purpose of this research to identity the types of code switching such as: tag switching, inter-sentential switching and intra-sentential switching found in one of Deddy Corbuzier podcast entitled Mereka Semua Bohong which released in 2020. This study conducted with observation method and analysed using qualitative and quantitative methods. The writers collected the data with several action such as watching the podcast several times, taking note the utterance that contain code switching and classify the utterance into types of code switching . To analyze the data, Poplack's (1980) concept was employed.